Families in Eastern Europe - Robila, Mihaela (Contemporary perspectives on family research ;, 2004)
Eastern Europe has been recognized as a region that has experienced major socio-political and economic changes in the last decades. The impact of these transitions on families and their functioning has also been significant. Although understanding of families in different cultures in the last years has been considerably increased, little has been written on Eastern European families. This book fills the void in literature and provides a timely and comprehensive analysis of family issues in Eastern Europe. It brings together scholars from fourteen Eastern European countries: Bulgaria, Czech Republic, former East Germany, Hungary, Latvia, Lithuania, Macedonia, Moldova, Poland, Romania, Russia, Slovakia, Slovenia, and Ukraine. The authors explain family processes in that particular country focusing on the historic, social and economic contexts and the impact they have on families. The authors also provide demographic information about families and discuss cultural traditions, marital and gender roles, parenting processes, family policy and programs within the society, and the state of research on family issues. As the society is trying to adopt a global perspective of the family, there is a need for people to gain an in-depth understanding of the world from a historical, socio-economic, political and cultural framework. This volume is an important reference work to be used by scholars and undergraduate and graduate students. It is a reader appropriate for use in courses and seminars on families and cultural diversity. The book also constitutes an excellent source of information for policy makers, foundations, governments and leaders of international family and/or youth organizations. Finally, the volume could be used by general readers interested in the dynamics of families in Eastern Europe. The book develops new insights and understandings on family issues.